Rationality in decision-making within interorganisational networks - Danylovych-Kropyvnytska, M.; Limański, A. (Lviv Politechnic Publishing House, 2017)
A networking structure is a natural phase in the evolution of organisational forms. An organisational form of a network is a set of interconnected structures and technological elements, i.e. individual economic agents, cultural and social values that arrange inter-organisational relations in a certain order and make network processes operate in a systemlike fashion. Effective joint work in inter-organisational networks suggests a need for a common goal, which is perceived to be a critical factor for joint activities. The paper studies the rationality of decisionmaking for inter-organisational networks. The analysis of behaviour within inter-organisational networks that consist of agents, like firms, entrepreneurs, governmental authorities, scientific centres, proves that group decisions are not always an optimal method to achieve a goal. There are certain tasks and circumstances when an authoritarian approach to problem solving is more sensible. It analyses a formalized model for joint choice, prevailing practice and rationality of group decisionmaking in order to reach a strategic balance within a network. The study summarizes key advantages and drawbacks in case a decision is made by a group.
Keywords: inter-organisational networks; rationality; decision-making procedures; strategic balance; cooperative game; coalition; 65.012.123